A newborn with 22q11.2 deletion without phenotypical features of Di George syndrome - Oli, Prasanna Babu; Shrestha, Manish; Baral, Suman; Joshi, Suchita Shrestha (Nepal Mediciti Medical Journal, 2024)
DiGeorge syndrome is a congenital primary immunodeficiency disorder resulting from failure of appropriate development of the third and fourth pharyngeal pouches during embryonic phase of development. DiGeorge syndrome usually presents with a clinical triad of immunodeficiency, congenital cardiac defects and hypocalcemia due to hypoparathyroidism. Here, we report a case of DiGeorge syndrome in a neonate with no associated facial dysmorphism and typical phenotype but initially presenting with apnea and suspected septic shock. Subsequent laboratory findings, clinical imaging and molecular genetic testing helped us to reach the diagnosis.